2008
DOI: 10.1007/s11883-008-0046-7
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease in women

Abstract: The rates of cardiovascular disease (CVD) have decreased significantly for men over the past few decades, but similar reductions have not occurred in women. Consequently, CVD remains the leading killer of women in the United States. Men usually develop heart disease earlier than women, but women develop heart disease more rapidly once menopause has occurred. A review of risk factors that are common between men and women demonstrates some notable sex-dependent differences. Many of these changes appear related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…A number of population studies have indeed shown that, at comparable age, women are characterized by a lower incidence of angina pectoris, myocardial infarction, and stroke than men. 1 This has contributed to the general medical belief that women are at low cardiovascular risk at least until they reach the menopause. One of the issues with this concept is this: do we potentially underestimate the real cardiovascular risk of women and thereby miss an opportunity to improve our ability to prevent cardiovascular complications in women?…”
mentioning
confidence: 99%
“…A number of population studies have indeed shown that, at comparable age, women are characterized by a lower incidence of angina pectoris, myocardial infarction, and stroke than men. 1 This has contributed to the general medical belief that women are at low cardiovascular risk at least until they reach the menopause. One of the issues with this concept is this: do we potentially underestimate the real cardiovascular risk of women and thereby miss an opportunity to improve our ability to prevent cardiovascular complications in women?…”
mentioning
confidence: 99%
“…Men usually develop heart disease earlier than women do, but women develop heart disease more rapidly once menopause has occurred. 6 Before menopause, women are relatively protected from ischemic heart disease and thromboembolism by their circulating estrogens, but this protection is lost after menopause. Through the effect of the menopausal transition, the morbidity and mortality from CVD in women are increased.…”
mentioning
confidence: 99%
“…Many of these changes seem related to the hormonal changes that occur during menopause, such as the development of hypertension, changes in lipid concentrations, and central adiposity. 6 It is noteworthy to mention that Asian Indian women may be comparatively worse off than men with regard to many of the risk factors for CHD. 11<13 As far as India is concerned, only a few studies have related menopause with conventional CVD risk factors in general.…”
mentioning
confidence: 99%
“…It was shown that the incidence of heart disease among women rapidly approaches that in men [Lee and Foody, 2008], and women lose the protective effect of estrogen on hearing after menopause [Tandon et al, 2001;Thompson et al, 2006;Hwang et al, 2008]. Therefore, it is reasonable to expect that the hearing of women could be more obviously affected by CVD.…”
Section: Discussionmentioning
confidence: 99%